Current outcomes of the bi-directional cavopulmonary anastomosis in single ventricle patients: analysis of risk factors for morbidity and mortality, and suitability for Fontan completion. (23rd February 2015) - François, Katrien; Vandekerckhove, Kristof; De Groote, Katya; Panzer, Joseph; De Wolf, Daniel; De Wilde, Hans; Bové, Thierry
Abstract: Objectives: The bi-directional cavopulmonary anastomosis forms an essential staging procedure for univentricular hearts. This review aims to identify risk factors for morbidity, mortality, and suitability for Fontan completion. Methods: A total of 114 patients undergoing cavopulmonary anastomosis between 1992 and 2012 were reviewed to assess primary – mortality and survival to Fontan completion – and secondary outcome endpoints – re-intubation, new drain, and ICU stay. Median age and weight were 8 months and 6.9 kg, respectively. In 83% of patients, 1–3 interventions had preceded. Norwood-type procedures became more prevalent over time. Results: Extubation occurred after a median of 4 hours, median ICU stay was 2 days; 10 patients (8.8%) needed re-intubation and 18 received a new drain. Higher central venous pressure and transpulmonary gradient were risk factors for new drain insertion (p<0.01). Higher pre-operative pulmonary pressure correlated with increased inotropic support and prolonged intubation (p=0.01). Need for re-intubation was significantly affected by younger age at operation (p=0.01). Hospital and pre-Fontan mortality were 11.4 and 5.3%, respectively. Operative mortality was independently affected by younger age (p=0.013), lower weight (p=0.02), longer bypass time (p=0.04), and re-intubation (p=0.004). Interstage mortality was mainly influenced by moderate ventricular function (p=0.03); 82% of survivors underwent or are candidates for Fontan completion. Conclusion: The cavopulmonary anastomosis remains associated with adverse outcomes. Age at operation decreases with rising prevalence of complex univentricular hearts. Considering the important impact of re-intubation on hospital mortality, peri-operative management should focus on optimising cardio-respiratory status. Once this selection step is taken, successful Fontan completion can be expected, provided that ventricular function is maintained.